Habitat filtering and niche differentiation jointly explain species relative abundance within grassland communities along fertility and disturbance gradients - Luca Borger (New Phytologist, 2012)
1.Deterministic niche-based processes have been proposed to explain species relative abundance within communities but lead to different predictions: habitat-filtering (HF) predicts dominant species to exhibit similar traits while niche differentiation (ND) requires that species have dissimilar traits to coexist. 2.Using a multiple trait-based approach, we evaluated the relative roles of HF and ND in determining species abundances in productive grasslands. Four dimensions of the functional niche of 12 co-occurring grass species were identified using 28 plant functional traits. Using this description of the species niche, we investigated patterns of functional similarity and dissimilarity and linked them to abundance in randomly-assembled six-species communities submitted to fertilization/disturbance treatments. 3.Our results suggest that HF and ND jointly determined species abundance by acting on contrasting niche dimensions. The effect of HF decreased relatively to ND with increasing disturbance and decreasing fertilization. Dominant species exhibited similar traits in communities whereas dissimilarity favored the coexistence of rare species with dominants by decreasing inter-specific competition. This stabilizing effect on diversity was suggested by a negative relationship between species overyielding and relative abundance. 4.We discuss the importance of considering independent dimensions of functional niche to better understand species abundance and coexistence within communities.